Benedict XVI : a guide for the perplexed - Rowland, Tracey (London ; New York : T & T Clark, 2010)
"This guide introduces students of theology to the theoretical axes upon which the theology of Benedict XVI revolves. It begins with a presentation of the key ideas in the works of his intellectual antecedents and contemporary interlocutors and then moves to an account of Benedict's responses to a number of theological crises."--P. [4], cover.